2009
DOI: 10.1111/j.1744-7402.2008.02274.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Tunable Dielectric Properties of (Ba0.7Sr0.3)TiO3‐Glass‐Based Thick‐Film Capacitors

Abstract: Ferroelectric glass-ceramics of composition 0.90 (Ba 0.7 Sr 0.3 ) TiO 3 -0.10(B 2 O 3 :SiO 2 ) (0.90 BST:0.10 BS) synthesized by sol-gel method have been used for the preparation of dielectric thick-film inks. The particle dispersion of the glass-ceramic powders in the thick-film ink formulations have been studied through rheological measurements for fabricating thick-film capacitors by screen printing technique. The thick films derived from such glass-ceramics are found to sinter at considerably lower tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The thick film derived from BST glass-ceramics has tunability of 32 % at 1 MHz under a dc bias field of 35 kV/cm. This result indicates that such glass-ceramic composition have significant importance in the application of tunable phase shifter [135].…”
Section: Lead Titanate Glass Ceramicsmentioning
confidence: 74%
“…The thick film derived from BST glass-ceramics has tunability of 32 % at 1 MHz under a dc bias field of 35 kV/cm. This result indicates that such glass-ceramic composition have significant importance in the application of tunable phase shifter [135].…”
Section: Lead Titanate Glass Ceramicsmentioning
confidence: 74%
“…A 35-m-thick film of the glass ceramic indicated n r of 32% at 35 kV/cm. 15) In most of these studies, however, few examinations were attempted to correlate the n r changes with some parameter of the fabricated BST-based materials.…”
Section: Tunable Property Of Thick-film Compositesmentioning
confidence: 99%
“…It was also demonstrated that a thick-film sample fabricated from a glass powder with Ba/Sr = 7/3 had 27.3% tunability at 5 GHz under 10 kV/cm bias voltage. 23) It is interesting to note that BST glass-ceramic samples including those reported elesewhere 15,24,25) possess fairly good tunability even though they are not highly densified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations